ChemInform Abstract: Engaging Electronic Effects for Atropselective [5 + 2]‐Photocycloaddition of Maleimides. Issue 44 (13th October 2016) - Raghunathan, Ramya; Kumarasamy, Elango; Jockusch, Steffen; Ugrinov, Angel; Sivaguru, J.
Abstract: The maleimides substituents′ effects on the regioselectivity are examined.